User and provider perceptions of service quality : an exploratiory study of a professional service : a thesis submitted in partial fulfilment of the requirements of Master of Business Studies at Massey University - Kavet, Molly (Massey University, 1991)
This study looks at service quality and its evaluation from users' and providers' perspectives. Applied research is conducted in a hospital diagnostic service, largely because of the high level of interest in issues of quality, and the technical and professional nature within the service. The focus of the study is on examining the development of conceptual frameworks of service quality and carrying out research on service quality in an operational setting. Both qualitative and quantitative research methods are used in this exploratory study. A survey of expectations and perceptions of service quality features is carried out on 74 customers and 7 providers of the service. Written and verbal comments on areas in which service quality may be improved from both groups are collated and coded. A series of survey statements is developed from the literature and from preliminary interviews as indicators of service quality features. Perceptions of customers are examined in relation to both the critical features of the service and perceptions on how the service performed in relation to each feature. The gap analysis is used to compare the views of the provider group with those of the customer group. The findings demonstrate that there are several areas where views are similar between providers and customers. In addition, areas are identified where differences exist between the importance ratings for service quality features and the evaluation of performance of the service in relation to these features. Factors which may influence the extent to which these differences exist are presented. It is suggested that a major reason for these differences is a lack of understanding of the evaluation of service quality and the importance of this evaluation on the strategic positioning of the service. It is concluded that although attention to clinical aspects of quality is important, a heightened awareness of the importance of service quality is needed by health service providers. Action taken by service providers to identify critical quality features and evaluate performance in relation to these features, can create opportunities for increased levels of customer satisfaction and the consequent likelihood of successful adaptation to changing environmental demands.
Keywords: Organizational effectiveness; Measurement; Customer services; Evaluation